Systematic theology ; v. 1 pts 1-4 - Chafer, Lewis Sperry, 1871-1952; Walvoord, John Flipse, 1910-; Campbell, Donald K.; Zuck, Roy B. (Wheaton, IL Victor, 1988)
Contents : v. 1 : pt 1: Bibliology; pt 2 : Theology proper; pt 3 : Angelology; pt 4 : Anthropology. Includes bibliographical references and index.
Originally published, 1947, in eight volumes.
Keywords: Theology, doctrinal